The role of thioredoxin system in cancer: strategy for cancer therapy - Jia, Jin-Jing; Geng, Wen-Shuo; Wang, Zhan-Qi; Chen, Lei; Zeng, Xian-Si (Cancer chemotherapy and pharmacology, 2019)
Purpose Cancer, a major public health problem, exhibits significant redox alteration. Thioredoxin (Trx) system, including Trx and Trx reductase (TrxR), as well as Trx-interacting protein (TXNIP) play important roles in controlling the cellular redox balance in cancer cells. In most cancers, Trx and TrxR are usually overexpressed and TXNIP is underexpressed. In recent years, some agents targeting Trx, TrxR, and TXNIP were used to explore a therapy approach for cancer patients. Methods A systematic search of PMC and the PubMed Database was conducted to summarize the potential of Trx system inhibitors for cancer treatment. Results In this article, we first summarize the functions of Trx, TrxR, and TXNIP in cancers. We also review some small molecule inhibitors of Trx/TrxR and d -allose (TXNIP inducer) and discuss their antitumor mechanisms. We highlight the combined inhibition of Trx system and GSH system in cancer therapy. We expect that a highly specific and selective antitumor agent with no cytotoxicity on human normal cells could be developed in the future. Conclusion In conclusion, Trx system may be very promising for clinical therapy of cancer in the future.